Global perspective on red chili drying: insights from two decades of research (2004–2023) - Elmatsani, Huda M.; Munarso, S. Joni; Benyamin, Boni; Budiyanto, Agus; Yohanes, Heryoki; Djafar, Mochammad Jusuf; Sjafrina, Noveria; Koeslulat, Ermi E.; Lukas, Amos; Lanjar, Lanjar; Arianto, Arief (Frontiers in Sustainable Food Systems, 2024)
In recent years, the drying of red chili peppers (Capsicum annuum) has garnered increasing attention in the global food industry, resulting in significant advances in drying techniques. This study presents a bibliometric analysis of red chili drying research from 2004 to 2023, using VOSviewer and Bibliometrix software. The analysis adopts a two-pronged approach: (1) research structure analysis, which maps collaborative networks among researchers, and (2) topic development analysis, which explores thematic evolution in this field. The results indicate a steady annual growth rate of 6.65% in publications, with major contributions from countries such as Turkey, India, and China. Drying technologies have advanced from traditional methods like sun drying to modern techniques, including solar, convective, infrared, ultrasound, radio-frequency, microwave, and freeze drying. These innovations not only improve efficiency but also help retain the sensory and bioactive qualities of chili peppers, such as color, texture, capsaicinoids, and antioxidants. Recent trends highlight the importance of optimizing processes to enhance product quality while minimizing energy consumption, contributing to food sustainability. Innovations in pre-treatment techniques, such as blanching and cold plasma, have also demonstrated potential in preserving bioactive compounds. Additionally, hybrid methods that combine drying techniques with pre-treatment strategies offer an optimal balance between efficiency and quality. The study recommends that future research focus on comparative analyses of different drying methods, examining their effects on product quality and energy efficiency. These insights aim to guide researchers, policymakers, and industry stakeholders in developing more sustainable and effective drying technologies for red chili.